De la calle al teatro y del teatro al texto - Vázquez Tourino, Daniel (Verba hispanica, 2024)
The article examines the forms of the theatricalization of violence in Latin American dramatic literature. One of the consequences of the ‘performative turn’ in the performing arts (Fischer-Lichte) is the prevalence of the contingency of the theatrical event in aesthetic experience, to the detriment of mimesis. Thus, in contrast to the illusion of reality in representation, the real presence of the audience and the artists is accentuated. How, then, does the dramatic text – which is mimetic by nature – reflect the primacy of the real over representation? Specifically, how does contemporary dramaturgy adopt the assumptions of the performative turn when dealing with the theme of violence? The paper will analyze the construction of the self-referential in Bárbara Colio’s play Usted está aquí, in order to understand the mechanisms through which dramatic writing contributes to the emergence of a “theatrical conviviality” (Dubatti) of audience and artist around the experience of violence in northern Mexico.
Keywords: Colio, Barbara; mehiška književnost; mehiško gledališče; Mexican theatre; mimesis; mimeziz; nasilje; violence